Case report: Guillain-Barré syndrome and possible association with Lyme disease - I. Muliuolis; E. Tilindytė; R. Samaitienė (Neurologijos seminarai, 2019)
Guillain-Barré syndrome (GBS) is an acute inflammatory demyelinating or axon-damaging polyneuropathy. It is characterized by sensory, motor and reflex disorder, damaged cranial nerves, autonomic disorders, and, less frequently, damage to the central nervous system. This is a life-threatening condition that urges patients to seek emergency treatment for progressive pain, paralysis and/or respiratory distress that can cause death in the absence of timely treatment. Early diagnosis and treatment of this condition are very important in preventing fatal outcome. Although many infections are associated with the etiology of GBS, correlation with Lyme disease is determined very rarely. Lyme disease is a tick-borne Borrelia burgdorferi infection that can cause lesions of multiple organ systems: usually the skin, joints, nervous system, and the heart. This case report presents an 8-year-old boy who was admitted to the hospital because of progressive weakness in the extremities, meningeal signs, bilateral facial nerve paresis, and areflexia. The patient was diagnosed with GBS and Lyme disease; and symptoms of the patient gradually disappeared following the treatment with intravenous immunoglobulin and ceftriaxone. Although the diagnosis of GBS was definite, the diagnosis of Lyme disease was complicated by a variety of circumstances which we analyse in this article. We also discuss a possible connection between the two pathologies.